PENGEMBANGAN POTENSI DESA SELONG BELANAK SEBAGAI DESTINASI WISATA - Hasan Basri; I Made Darma Oka; I Wayan Lanang Nala; Putu Widya Darmayanti; I Wayan Sukita (Jurnal Kajian dan Terapan Pariwisata, 2024)
This research examines the potential of Selong Belanak Village to be developed into a tourist destination in Central Lombok. Data collection methods include observation, documentation, interviews and focus group discussions. Informants were determined using purposive sampling. Data analysis were carried out by using qualitative and quantitative analysis through SWOT analysis to examine strengths, weaknesses, opportunities and challenges faced in the future. The results of the SWOT analysis of Selong Belanak village show that from the internal side the results are in the good category with a value of 3.10, as well as from the external analysis side it is in the good category with a value of 3.06. This means that this village has the potential to be developed into a tourist destination. It is recommended that the development of this tourist destination must be carried out by synergizing all relevant pentahelic actors (government, academics, business people, the media and local communities).